Learning To Live Together: Penanaman Karakter pada Anak Usia Dini di Lembaga PAUD Islam - Ismail SM; M. Agung Hidayatulloh (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
This paper explores about 1) the importance of application pillar of â€œLearning to live togetherâ€ as an effort to implement character on children under five years at PAUD Islam schools; (2) learning activities which reflect the application pillar at PAUD Islam institution; and (3) kind of characters which are built as the effect of the application pillar on children under five at PAUD Islam schools. In this paper, the qualitative research data was obtained from the teachers of PAUD (RA) through questionnaire distribution. The research result showed that pillar â€œLearning to live togetherâ€ remains importance to be implemented on children under five years old, particularly at PAUD Islam schools. It is because of early years period is a golden age for children to reserve all aspects which they learned and saw. Also it is based on Qurâ€™anic teachings. Among the activities which reflected the application pillar are beam playing, sightseeing, role playing, and heroic stories.Therefore, the character values should be wholly implemented on the children under five years old which can be built through the application pillar on â€œLearning to live togetherâ€.